Investment preferences of the population of Ukraine: response to shocks of martial law - Bereslavska O. I.; Shyshkov S. Ye.; Sheludko N. M. (Український соціум, 2022)
The article contains the results of the analysis of the investment behaviour of Ukrainian households in the crisis caused by external armed aggression. The financial potential of Ukrainian households in the pre-war period was assessed, and it was concluded that the expenses of most of the population were directed to the consumer rather than investment purposes. It was found that the investment potential of households was directed, first, to the purchase of currency, real estate, and deposits, as well as to risky crypto-currency assets, the active use of which Ukraine is one of the world leaders, instead of public investments in securities and other financial instruments remain extremely limited. The choice of the population of Ukraine in favour of investments in currency, real estate, deposits, and government bonds is currently quite rational since investments in private instruments of the local capital market (both directly and through pension funds and mutual investment institutions) do not provide high profitability and are associated with significant risks. It was revealed that in the conditions of martial law, the investment priorities of the population were most affected by the need to protect savings from depreciation, finance the country’s defence needs, and the corresponding rate of growth of the state debt, as well as high risks of real estate investments and strict restrictions of the National Bank of Ukraine on capital movement. It has been established that at a relatively high level of inflation, Ukrainian citizens do not receive a deposit offer from banks that is adequate to maintain the solvency of their savings. A situation in the banking system that is dangerous for financial stability has been identified, which is associated with the formation of a liquidity “canopy” due to the balances on the current accounts of the population. Emphasis is placed on the need to urgently increase the reserve requirements for demand deposits and current deposits to stimulate the growth of the value of hryvnia assets and change the banks’ liquidity surplus structure. Prospective directions and tools for the placement of household savings are justified, considering the needs of the post-war recovery of Ukraine’s economy and the prospects for European integration.